PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SDN 002 PAGARAN TAPAH DARUSSALAM - Silalahi, Yusnidar (EDUTECH CONSULTANT, 2017)
This research is motivated by the low learning outcomes Civics Grade IV SDN 002 Pagaran Tapah Darussalam. Goals to be achieved in this research is to improve student learning outcomes Civics Class IV SDN 002 Pagaran Tapah Darussalam through the Use Media Pictures conducted during one month. This research was conducted in SDN 002 Pagaran Tapah Darussalam. Classes that thorough research is a Class IV second semester the number of students as many as 24 people. This form of research is classroom action research. Based on the analysis and discussion as presented in chapter IV can be concluded that the use of media images can improve learning outcomes of fourth grade students in civic education subjects in SDN 002 Pagaran Tapah Darussalam. It can be seen from the changes in student learning outcomes in cycle 1 and cycle 2. In cycle 1 average student learning outcomes in 66.7 siklus1adalah the category is not exhaustive and experience peningkata in cycle 2 to 84.2 by category completely. The number of students that scored above 70 (Complete a minimum) in the first cycle were 12 people (50%), while in the second cycle increased to 22 (91.6%). Based on the performance indicators that this research is successful when learning completeness reached 75% of all students